PANCASILA, DEMOKRASI LIBERAL DAN KOMUNITARISME - Otto Gusti Madung (Jurnal Ledalero, 2014)
The domcratisation process which has been pursued by the Indonesian nation since the reformation era is now caught up in a procedural democracy without the wellbeing of the people or social justice. Proceduralism is the most basic criticism of liberal democracy by republicans and communitarians. From a communitarian perspective, the Pancasila state ideology as the normative base and collective identity of the Indonesian nation is able to offer a way out of the crisis of liberal democracy as practised in Indonesia. This essay attempts to show that it is not an effort to build a democratic order upon procedural ethics as is assumed by liberals, but rather the need to provide a substantial ethical foundation. This is the case as a democratic system is not filled with atomistic individuals but with social relationships. A democratic process always moves within a society shaped by social relationships and various complex processes for the formation of communities. Democracy is built upon a collective identity which is formal yet fragile. In the Indonesian context, the Pancasila is the collective expression the nation’s identity. As a collective identity, the Pancasila will never be complete, but will always be in a state of becoming rediscovering itself anew. In the final section, two methods are presented, namely the method of deliberative and agonistic democracy as a way proposed by contemporary political philosophy in overcoming conflicts in values in the face of pluralism. The Pancasila will become the collective identity which animates the people of Indonesia, only when it is open to a process of rational deliberation in the public sphere and is ready to be only one alternative in the midst of a competitive discourse. Kata-kata kunci: liberalisme, komunitarisme, Pancasila, identitas kolektif, demokrasi, deliberasi, agonistik.